A pilot study of behavioral and physiological markers of stress in horses during equine-assisted learning for youth with social-emotional concerns - Singh, Ashley, author; Grandin, Temple, advisor; Peters, Caiti, advisor; Matlock, Sarah, committee member; Nett, Terry, committee member (Colorado State University. Libraries, 2023)
Equine Assisted Learning (EAL) is an increasingly popular service in providing comfort and life skills for youth who have social-emotional concerns. There is mixed evidence in previous research that shows increased stress in horses in EASs who are interacting with the population of youth with social- emotional concerns. This pilot study aimed to look physiological and behavioral indicators of stress in horses involved in equine assisted learning for youth with social- emotional concerns. This within-subject design included 11 horses and 18 human participants. Indicators of equine stress included salivary cortisol, eye temperature, and equine behavior. On average, indicators of stress in horses were not significantly different while the horses interacted with youth with social- emotional concerns compared to a control condition. There was a significant condition x week interaction effect such that horses demonstrated higher levels of cortisol in week 3 while interacting with youth with social- emotional concerns compared to the control condition, but this difference did not exist by Weeks 5 and 7. These condition by week interaction effects did not exist in equine eye temperature or behavior. This study provides evidence that interacting with youth with social- emotional concerns was not more stressful for horses that interacting with another population that commonly participates in EAL.
Keywords: behavioral; equine assisted services; youth with social-emotional concerns; equine assisted learning; animal assisted therapy; physiological